Method for the registration and analysis of aerial images, applied to the architecture of construction sites, using low-cost devices - Aguilar Paredes, Richard Eddgar (2022)
FPGA-based hardware architectures are being used more frequently in many applications, thanks to the different programming languages that allow us to access them. The applications are also being varied, one of the most common areas of work with aerial images, normally acquired with cameras that are on board drones, the working mode of these configurations, is focused on being able to use visualize the images online As the flight is carried out, if you want to carry out some type of processing, it is necessary to download the image from the camera's memory, this process is already carried out when the drone has finished the flight. In this work we present a methodology to be able to use the low-cost hardware myRIO, since it has a processor and an FPGA included, we present the steps to be able to work with the device, as well as an example of online processing so that the video and images that the drone camera can process on board and transmitted online, so that images and videos are processed while the drone is in flight, thereby improving the performance of the drone and can be applied In special operations, as a result we present the device configuration and the results of an example.